Integrating Social Presence With Social Learning to Promote Purchase Intention: Based on Social Cognitive Theory - Li, Miao; Hua, Ying (Frontiers in Psychology, 2022)
Consumers mainly acquire information through social learning in online shopping environment, and social presence as a media attribute generated by real-time interactions in live streaming commerce is more conducive for consumers’ social learning. Therefore, it is worth investigating the roles of social presence and social learning on consumers’ purchase intention in the strong interactive environment. Based on social cognitive theory framework and drawing on social presence theory and social learning theory, the current study investigates the relationships between social presence, social learning process and purchase intention. Social presence is operationalized into social presence of others and social presence of interactions, whereas social learning process contains external interaction process (exploitative learning and exploratory learning) and internal psychological process (cognitive appraisal and affective appraisal). The results from a survey of 372 consumers of live streaming commerce indicate that social presence of others and social presence of interactions positively affect exploitative learning and exploratory learning, and then contribute significantly to the building of cognitive appraisal and affective appraisal, which can lead to purchase intention. The findings also provide brand managers and retailers guidance in building more effective interactive atmosphere and promoting consumers’ positive attitude toward brands in live streaming marketing.